Perempuan Sumber Sial Dalam Hadis Shahih Bukhari Nomor 5903 (Kajian Tahlili) - Ahmad Fikri; M. Rizki Syahrul Ramadhan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research discusses the hadith in Sahih Bukhari that narrates that one of the places of misfortune is women. Textually, this hadith is controversial as it is perceived to contain misogynistic suggestions conveyed by the Prophet Muhammad (peace be upon him). The purpose of this research is to comprehensively understand the process of transmission and the scholars' interpretation of this hadith. Additionally, this research also attempts to interpret the hadith through the contemporary Fiqh al-Hadith methodology proposed by contemporary scholars. The researcher employs a qualitative inductive method, obtaining data and information by collecting classical Islamic texts, including those that specifically explain the related hadith as well as other relevant books. These include books on hadith terminology, hadith commentaries, hadith text, and hadith narrator studies, among others. This research finds that the Sahih Bukhari hadith number 5093 is of hasan quality. This hadith also has many corroborating and supporting narrations of better grades. Meanwhile, the meaning of misfortune contained in it, according to the majority of scholars, is attributed to women temporarily and not permanently. Misfortune is associated with women when they have bad character, infertility, and other non-permanent negative traits. In the mubadalah (reciprocal) method, misfortune is not only attributed to women but also to men, as men can also experience infertility, bad character, and other non-permanent negative traits.